An analysis of active consumer behavior in a fitness boutique: satisfaction levels, perceived quality dimensions, and dropout reasons - Silvio Addolorato; Nerea Hormigón-Gimeno (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The European fitness market is experiencing continuous growth, prompting enhancements in service quality at boutique gyms. These establishments are recognized for their personalized attention, professional staff, and innovative technology use. The perceived quality in these gyms significantly influences client satisfaction and loyalty, which are critical for retention. The aim of the contribution is to understand satisfaction levels, perceived quality dimensions, and dropout reasons inside this business model. The study sample comprises 67 adults, aged 18 to 70 years, predominantly aged 41-50. The EPOD2 Questionnaire and Dropout Reasons Scale were utilized for data collection. An analysis of a boutique fitness center in Zaragoza (Spain), indicates high demand, particularly among women. Most users positively rate the service, especially commending the staff, though communication is rated lower. Higher satisfaction is associated with increased loyalty, and reasons for dropout include distance and congestion, consistent with previous studies. The study has some limitations, including: sample size, gender imbalance, and a lack of longitudinal data. Further approaches should encompass larger samples, longitudinal designs, and broader comparisons to enhance the understanding of satisfaction and loyalty in boutique fitness centers.